2007
DOI: 10.1080/03098260601063628
|View full text |Cite
|
Sign up to set email alerts
|

Fieldwork is Good: the Student Perception and the Affective Domain

Abstract: This paper reports on research that investigates the effectiveness of residential field courses in geography, earth science and environmental science courses at UK institutions of higher education. The research focuses on the effects of fieldwork in the affective domain, which is thought to be linked to the adoption of effective approaches to learning. Approximately 300 students were surveyed immediately before and after a field class, enabling analysis of changes in responses brought about as a result of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
243
4
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(270 citation statements)
references
References 25 publications
11
243
4
3
Order By: Relevance
“…Amongst these is the claim that it can usefully enhance the causal link between student affective response (emotions, feelings and values) and deep learning (Higgitt, 1996;Fuller et al, 2006;Boyle et al, 2007). Evidence from educational psychology has suggested a relationship between fieldwork and enhanced cognitive and affective gain (Foskett, 1999), and Carpenter (1984, 1986) demonstrated that fieldwork increased the enjoyment of geology students and the value they gave to the subject.…”
Section: Introduction: Fieldwork As a Privileged Mode Of Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst these is the claim that it can usefully enhance the causal link between student affective response (emotions, feelings and values) and deep learning (Higgitt, 1996;Fuller et al, 2006;Boyle et al, 2007). Evidence from educational psychology has suggested a relationship between fieldwork and enhanced cognitive and affective gain (Foskett, 1999), and Carpenter (1984, 1986) demonstrated that fieldwork increased the enjoyment of geology students and the value they gave to the subject.…”
Section: Introduction: Fieldwork As a Privileged Mode Of Learningmentioning
confidence: 99%
“…To some extent this is being addressed (May, 1999) and there is now a sizeable literature on geographic fieldwork (Gold et al, 1991;McEwen, 1996;Kent et al, 1997;Cottingham et al, 2002;Robson, 2002;Fuller et al, 2003;Fuller et al, 2006;Boyle et al, 2007). Consequently Fuller et al (2006) have recently concluded that while there still remains the need for research into the relationship between fieldwork and student learning "the pedagogy of fieldwork has moved on" (Fuller et al, 2006, p. 93).…”
Section: Introduction: Fieldwork As a Privileged Mode Of Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Wright & Hodge (2012) describe the emotional geographies of cross-cultural e pe ie es o fieldt ip as a p ofou d lea i g e pe ie e edole t ith e otio which is t a sfo ati e a d halle ges stude ts o pe spe ti es of so ietal o e tio s a d di e sit . Boyle et al (2007) report that, whilst experiencing some apprehension and anxiety, students recognise the positive outcomes of being challenged by an unfamiliar environment. This is further explored by Glass (2014), examining how local and external factors can generate positive and negative experiences that may affect stude ts e pe ie es of a pa ti ula pla e o t ip.…”
Section: Introductionmentioning
confidence: 99%
“…Not only do students have to comprehend the geography of an unfamiliar environment, but often have to deal with their own relationships towards that place. Studies have focused on the affective domain and ho the lea i g a d tea hi g st ategies adopted a i flue e stude ts e gage e t ith the fieldwork locality (Boyle et al, 2007;van der Hoeven Kraft, Srogi, Husman, Semken & Fuhrman, 2011). Savin-Baden (2008: 7) describes learning spaces as pla es of e gage e t he e ofte dis o e ted thoughts a d ideas, that ha e ee i hoate, egi to ohe e as a esult of ei g i a pla e o position that stimulates a creative shift in perception or understanding.…”
Section: Introductionmentioning
confidence: 99%